Clinical comparison of a self-etching fissure sealant with a conventional sealant: A 12-month follow-up - Shahrzad Javadinejad; Parvin Mirzakoucheki Borojeni; Morteza Saleki; Fatemeh Hajizadeh (مجله دانشکده دندانپزشکی اصفهان, 2012)
AbstractIntroduction: Self-etching fissure sealants have been introduced recently, leading to elimination of etching and rinsing, reducing working time and consequently increasing child cooperation. This clinical study was conducted to compare the retention rate, caries occurrence and marginal integrity of a self-etching fissure sealant (Prevent Seal) with a conventional sealant (Concise) over a12-month period. Materials and methods: In this clinical trial 192 first permanent molars of 48 children aged 7-9 years were selected. Self-etching sealants were randomly used for first permanent molars on one side of the mandible and contralateral side of the maxilla and conventional sealants (etch-and-rinse) were placed on the remaining first permanent molars. Clinical evaluation was performed at 3-, 6-, and 12-month intervals by a single blind examiner. The retention was classified as complete retention, partial loss and total loss. Caries incidence was assessed. Marginal integrity of sealants was also evaluated with modified U.S. Public Health Service (USPHS) codes. Data were analyzed with Friedman’s, Wilcoxon’s signed rank and McNemar’s tests using SPSS statistical software (α=0.05).Results: At the end of 12 months Concise had higher retention rates (87.5%) than Prevent Seal (12.5%), with statistically significant differences (p value < 0.001). Regarding marginal integrity of the sealants, Concise yielded significantly better results than Prevent Seal at all the follow-up examinations (p value < 0.001). However, there were no significant differences in caries incidence between the two groups (p value = 0.99).Conclusion: The results indicated that retention rate and marginal integrity of self-etching sealants are less than those of conventional ones at 12-month evaluation period. Key words: Clinical trial, Pit and fissure sealants, Tooth marginal integrity.